Impact of touring, performance schedule, and definitions on 1-year injury rates in a modern dance company. Issue 21 (2nd November 2017) - Bronner, Shaw; Wood, Lily
ABSTRACT: There is ongoing debate about how to define injury in dance: the most encompassing one or a time-loss definition. We examined the relationship between touring, performance schedule and injury definition on injury rates in a professional modern dance company over one-year. In-house healthcare management tracked 35 dancers for work-related musculoskeletal injuries (WMSI), time-loss injuries (TLinj), complaints, and exposure. The year was divided into 6 segments to allow comparison of effects of performance, rehearsal, and touring. Injuries/segment were converted into injuries/1000-h dance exposure. We conducted negative binomial regression analysis to determine differences between segments, P  ≤ 0.05. Twenty WMSI, 0.44 injuries/1000-h, were sustained over one-year. WMSI were 6 times more likely to occur in Segment-6, compared with other segments (incident rate ratio = 6.055, P  = 0.031). The highest rate of TLinj and traumatic injuries also occurred in Segment-6, reflecting concentrated rehearsal, New York season and performances abroad. More overuse injuries occurred in Segment-2, an international tour, attributed to raked stages. Lack of methods to quantify performance other than injury may mask effects of touring on dancer's well-being. Tracking complaints permits understanding of stressors to specific body regions and healthcare utilisation; however, TLinj remain the most important injuries to track because they impact other dancers and organisational costs.